Comunicação, educação e consumo: o processo de recepção do livro paradidático “Você precisa de quê?” por estudantes do Ensino Fundamental II - Antonacci, Andréa Celeste Montini (2021)
The object of this thesis are the Middle Grade students speeches about consumption, consumerism and advertising, based on the process of reception the paradidactic book Você precisa de quê?: a diferença entre consumo e consumismo. The construction of this object is based on the considerations from the field of communication / education / consumption about the importance of communicators and educators in the construction of social meanings about consumption and its universe that go beyond common sense, based on stereotyped and reductionist readings, towards more complex and scientific conceptions. To consider consumption as a significant cultural practice that crosses our daily lives and that contributes to the reproduction and production of society. Our research is at the confluence between studies on consumption and studies on Latin American reception. To tie these two fields of knowledge, we made use of contributions from the field of communication / education / consumption. In our path, we propose: a) to analyze the social and historical context in which that book is produced and posted in circulation; b) understand the discourse of this book: its internal forms, its patterns and relations of meaning; c) understand the process of receiving the book by elementary school students in the city of São Paulo. As a procedure for collecting primary data, we operate with three research techniques, namely: a) reception study stimulated through reading the book; b) short text written by the students about their readings and impressions on the book; c) semi-structured open interview. For the analysis of these speeches presented in the book and in the students' speeches, we rely on the French Discourse Analysis (FDA) references. Although limited study, as a conclusion, we understand slips of meaning that bring both conceptualization and resignification of the terms consumption and consumerism closer together. In the ideological context, we verified reproductions of reducing and moralistic views of consumption, but we also found spaces for the redefinition of their understanding.